O protagonismo das mulheres camponesas na luta pela terra - Silva, Ivanilson Batista da (2016)
This study aimed to analyze the role of rural women in the struggle for land in Amarela I is II settlements in the municipality of São Miguel de Taipu-PB, from 1993 to 1995. He sought also understand this as do action and results of social change, with regard to man and woman relationship, given that the act of collective struggle, women rewrote pre-established routes that determined their place in society. In this sense, there have been modifying agents of history, conquering themselves through the organization, the right to freedom to participate in cultural, historical, economic and political society. Because it is a qualitative research, whose protagonists subjects are women, it was decided to examine the data, content analysis (CA) according to Bardin (2006), which has guided the assessment of speech and meanings within the context of the fight in the effectiveness of the role of women. While procedural techniques were used bibliographic and documentary research, in addition to interviews guided by a semi-structured script. In its development, the analytical categories were discussed as: leadership, gender relations, the Rural Women's Movement, the struggle for land, feminism. The results showed that, in the exercise of their role, women turned, in a timely manner, a macho cultural factors that shaped it to be less. So rewrote preestablished routes that determined the place of women. The closing remarks, points to the fact that the struggles undertaken by them are characterized also as a current event to it that, in its fullness, they conquer the right to gender equality.